The Personal Make-up of the Vilnius Fatebenefratelli in the Second Half of the 17th and the 18th Centuries - Jakulis, Martynas (Lietuvos istorijos studijos, 2019)
This article addresses the fluctuations in the annual numbers of candidates accepted into the noviciate of the Fatebenefratelli, the numbers of novices who took vows, and those who withdrew from the noviciate by their own choice or were rejected; the age structure of novices, their geographical and social origins. The main sources for the study of the personal make-up of the Vilnius Fatebenefratelli (Ordo S. Joannis de Deo) are two books of novices (libri novitiorum) (1678‒1725, 1761‒1823) that supply the relevant personal information on 243 novices. The analysis revealed that 51% of the novices had successfully completed the noviciate, while others resigned by their own will or were rejected. Most candidates were aged between 18 and 37; however, the order’s internal structure and the short formation of novices allowed to accept older candidates. Most novices originated from the Grand Duchy of Lithuania, and mainly from the Vilnius, Navahrudak, Trakai palatinates and Samogitia. Most probably, this reflected the general trends of immigration to Vilnius as well as the lack of opportunities for religious vocations in Samogitia. The geographical origins of novices also show that candidates came from mainly rural localities, whereas only 30 originated from cities (including Vilnius) and towns. The sources do not adequately reveal the social origins of novices, and only sporadic mentions reveal some candidates to have come either from the nobility, towns- and tradespeople, or other groups. Nonetheless, considering their geographical origins and material status, it could be assumed that the majority of novices were of non-noble birth and originated from rural strata.
Keywords: Fatebenefratelli; the religious; Vilnius; registers of novices; noviciate